Effects of the Philippine political crisis in the banking industry in Iloilo City - Bandoja, Malbert; Castro, Rose Kathryn; La-anan, June; Salazar, Nicholei
The scandal that beset the country caused the economy its downfall. ForEx rates have gone sky high - businesses have gone dragging - inflation became the consumer's nightmare - banks have closed, declared bankruptcy or just showed notable slowness. This paper exposes the effects of the crisis in the banking industry in the following aspects : loans/financing (lending rates, loan portfolio, loan amortizations), deposit levels (Current Account/Savings Account, Time Deposits, Money Market Placements), Foreign Currency Transactions, bankruns, mergers, universal banks, and confidence. All these, in the context of Iloilo City and the banking attitude of Ilonggos. Loans/financing, deposit levels and foreign currency transactions have increased due to the scandal. Research has showed that bankruns are effects of the crisis while mergers are not. Universal banks are those banks which has been significantly influenced during the crisis. Nevertheless, confidence has remained in the banking industry. Ilonggos have severed transactions with some banks but still look forward to transactions with other banks. It shows the necessity, and not the luxury, of a banking institution. Interest levels and the marketing aspect of banks (counteraction strategies) also form part of the research.